2017
DOI: 10.1089/jpm.2016.0231
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated with In-Hospital Death among Commercially Insured Decedents with Cancer

Abstract: In-hospital deaths are common among commercially insured cancer patients. Patients with hematologic malignancy and patients who die without receiving hospice services have a substantially higher incidence of in-hospital death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Patients with a survival of <7 months, which corresponds to 50% of our cohort, had a risk of hospital death more than twice that of patients with a survival of �17 months. This indicates that time since diagnosis is an important factor for quality of EOL care, in line with earlier research [45][46][47]. Kelly et al showed that patients with lung cancer who died within 30 days of diagnosis were more likely to die in hospital compared to long-term survivors [48], and Brooks el al.…”
Section: Plos Onesupporting
confidence: 71%
See 1 more Smart Citation
“…Patients with a survival of <7 months, which corresponds to 50% of our cohort, had a risk of hospital death more than twice that of patients with a survival of �17 months. This indicates that time since diagnosis is an important factor for quality of EOL care, in line with earlier research [45][46][47]. Kelly et al showed that patients with lung cancer who died within 30 days of diagnosis were more likely to die in hospital compared to long-term survivors [48], and Brooks el al.…”
Section: Plos Onesupporting
confidence: 71%
“…Kelly et al showed that patients with lung cancer who died within 30 days of diagnosis were more likely to die in hospital compared to long-term survivors [48], and Brooks el al. found a negative association between survival time and in-hospital death, with patients surviving <6 months having the greatest risk [46]. Although some hospitalizations might be necessary, and might benefit patients during the EOL, hospitalization is considered suboptimal with regard to quality of EOL care [49] and the hospital is reported to be the least preferred location of death among patients [50].…”
Section: Plos Onementioning
confidence: 99%
“…19 We found that 33% of younger patients died in the hospital, comparable to the 28% observed in a study of commercially insured patients with cancer who died between July 2010 and December 2013. 13 Although chemotherapy use in the last days of life among Medicare enrollees has stayed steady over time at approximately 4.5%, 20 we observed a downward trend over time. This may have been caused by increased acceptance of palliative care interventions or a reduced offering of chemotherapy by practitioners.…”
Section: Discussionmentioning
confidence: 63%
“…Studies describing care patterns for patients with cancer who are younger than 65 years of age have focused on Medicaid recipients, 10 enrollees in a single integrated delivery system, 11,12 or commercially insured patients at a single tertiary center. 13 Using this unique database, we describe patterns of care in this population of commercially insured adults in western Washington State and identify areas for care delivery enhancement and future interventions to improve end-of-life care for patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, much of this research has focused on patients with solid tumors and may not be generalizable to those with hematologic malignancies, who are less likely than solid tumor patients to receive consultative palliative care or enroll in hospice and more likely to receive disease-oriented end-of-life care or die in the hospital. [4][5][6][7] While a few studies evaluate the feasibility and impact of palliative care interventions on patients with hematologic malignancies, 8,9 relatively little is known about their unique palliative care needs. Moreover, the category of hematologic malignancy encompasses a multitude of disease entities and patient populations that require individualized study.…”
Section: Introductionmentioning
confidence: 99%